Low-temperature applied to rice seed storage: an efficient protection method against fungal contamination - Aguiar, Raimundo Wagner Souza; Brito, Deyvid Rocha; Nascimento, Vitor L; Fidelis, Rodrigo Ribeiro; Ferreira, Talita Pereira de Souza; Santos, Gil Rodrigues (Revista de Ciencias Agrícolas, 2020)
Low-temperatures have long been thought to enhance seed health during storage. Here we tested the effect of low-temperature on the mycoflora associated with rice seeds. Seeds of the IRGA 423 and 424 cultivars were stored in refrigeration (8 and -50°C) or at room temperature (25 ± 10°C). Following storage (1, 45, and 90 days) was investigated the fungi associated with the seeds. We found that, for both cultivars, low-temperature stored seeds had a lower fungal load than the seeds at room temperature. After 90 days of storage, there is a decrease in its incidence rate average of more than 85% in the lower temperature (-50°C). All mycroflora was eliminated at 90 days except for Fusarium sp. The Trichoderma sp. was detected only in IRGA 423 seeds, whereas all other fungi were detected in the treatments in both cultivars. Only Bipolaris sp. was observed in seed-to-seedlings transmission analyses, in both cultivars, at 8°C, and was not detected at -50°C. Based on our results, we recommend low-temperature storage (at -50ºC) of rice seeds.